The effect of vocabulary learning strategy training on vocabulary strategy use - Abebaw Dessalew Bayabel; Nuru Mohammed Tahir (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
Nowadays, it is recommended to train students on how to learn vocabulary, for it is not practicable to teach all the English language words. The purpose of this article was to find out the effect of vocabulary learning strategy training on vocabulary learning strategy use of university students. The research design used in this study was experimental. 40 students (20 students in each group) from both experimental and control groups completed the adapted Schmitt’s (1997) Vocabulary Learning Strategies Questionnaire (VLSQ) before and after the vocabulary learning strategy training. After the students completed the pre-training questionnaire, only the experimental group learners received vocabulary learning strategy training for 16 hours. The researcher prepared the vocabulary strategy training material by integrating the vocabulary lessons incorporated from different books. Paired samples t-test was computed on SPSS version 24 to find out if there was a statistically significant difference between the experimental and control groups regarding vocabulary learning strategy use. The study found that the experimental group participants improved their vocabulary usage significantly better than the control group participants in the five among six major categories of vocabulary learning strategies (less than the p-value of 0.05). Future researchers can study the effect of training in learning strategies of other language skills and sub-skills and can improve their strategy usage. One of the significance contributions of this study could be curriculum designers might employ this article as an input to incorporate vocabulary learning strategies into English language training materials and improve students’ vocabulary strategy use.